2023
DOI: 10.1186/s12905-023-02411-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational intervention based on theory of planned behaviour on promoting preventive behaviours of oral cancer in rural women

Abstract: Background Oral cancer has created an alarming situation around the world, and being the 16th most common cancer worldwide, it has become a global concern. The present study aimed to investigate the effect of educational intervention based on a theory of planned behavior (TPB) on promoting preventive behaviors of oral cancer in rural women. Methods This quasi-experimental study was conducted on 120 female hookah users referring to rural health cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(36 reference statements)
2
2
0
Order By: Relevance
“…Consistent with our results, a number of national and international studies have confirmed the significant impact of educational interventions on improving knowledge about oral cancer [ 12 , 19 , 20 , 28 , 29 ]. However, our findings stand in contrast to an RCT conducted among Taiwanese with a history of betel quid chewing and smoking.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our results, a number of national and international studies have confirmed the significant impact of educational interventions on improving knowledge about oral cancer [ 12 , 19 , 20 , 28 , 29 ]. However, our findings stand in contrast to an RCT conducted among Taiwanese with a history of betel quid chewing and smoking.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, consistent with the results of many previous studies [ 19 – 22 , 31 – 34 ], positive changes in knowledge, behavior, and the related constructs over time could be interpreted according to the theory concepts. The decrease in tobacco smoking could be attributed to the application of TPB, which is widely recognized as an effective model for facilitating sustainable behavioral change [ 15 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The use of tobacco and heavy alcohol drinking are the two most important risk factors for OSCC [ 31 ], and other known risk factors including areca nut, narcotics, epigenetic factors and viral infections [ 32 , 33 ]. In this study, multivariate analysis proved that tobacco was an independent factor for poor prognosis in OSCC patients and there was no statistically significant difference for alcohol and OS.…”
Section: Discussionmentioning
confidence: 99%